2019
DOI: 10.3390/cryst9110591
|View full text |Cite
|
Sign up to set email alerts
|

Review of Size Effects during Micropillar Compression Test: Experiments and Atomistic Simulations

Abstract: The micropillar compression test is a novel experiment to study the mechanical properties of materials at small length scales of micro and nano. The results of the micropillar compression experiments show that the strength of the material depends on the pillar diameter, which is commonly termed as size effects. In the current work, first, the experimental observations and theoretical models of size effects during micropillar compression tests are reviewed in the case of crystalline metals. In the next step, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The exceptionally higher nano-indentation stresses and especially the significantly higher strain hardening coefficients obtained both for the current (111) and (100) α-iron crystal surfaces-as well as for the earlier-described AP strength properties described for {210} crystal surfaces-relative to microand macro-indentation properties or test measurements on conventional bulk materials, relate generally to the particular higher stress environments involved with the much smaller dislocation line lengths that are operative at nano-scale dimensions [26,27]. A main contribution to the higher strength values has been more often associated therefore with the Taylor theory of flow stress dependence on the dislocation density.…”
Section: Discussionmentioning
confidence: 60%
“…The exceptionally higher nano-indentation stresses and especially the significantly higher strain hardening coefficients obtained both for the current (111) and (100) α-iron crystal surfaces-as well as for the earlier-described AP strength properties described for {210} crystal surfaces-relative to microand macro-indentation properties or test measurements on conventional bulk materials, relate generally to the particular higher stress environments involved with the much smaller dislocation line lengths that are operative at nano-scale dimensions [26,27]. A main contribution to the higher strength values has been more often associated therefore with the Taylor theory of flow stress dependence on the dislocation density.…”
Section: Discussionmentioning
confidence: 60%
“…For BCC crystals with the ©100ª orientation, log(¸c/G) vs. log(D/b) plots are more variable than those of FCC crystals. The distribution of the data points of the critical shear stress for all the BCC crystals collected by Shahbeyk et al 23) expands over a wide band region with a negative slope. The width of the distribution is not much different from that of FCC metals, but what is different is that the distribution of the data points of BCC metals is more or less uniform in the band, in contrast to the rapidly decreasing point density away from the theoretical curve in FCC metals.…”
Section: Bcc Micropillar Crystals With ©100ª Orientationmentioning
confidence: 95%
“…According to the comprehensive review by Greer and De Hosson, 22) the slope of the line best fitted to log(¸c/G) vs. log(D/b) plots for a number of FCC metals data is about ¹0.65. The fitting for the more collected data for FCC crystals in the latest review by Shahbeyk et al 23) indicated m µ ¹0.64. Thus, it is safe to say that the exponent for FCC metal crystals is in-between ¹0.6 and ¹0.7.…”
Section: Introductionmentioning
confidence: 99%
“…The same dependence has been found for integrated circuit-connected measurements on gold micro-wires [21] as well as for thin copper wires [22] and other nickel nano-pillar [23] materials, also with consideration taken into account of the nano-polycrystal grain structures. The status of nano-polycrystal micro-pillar strength properties have been reviewed by Shahbeyk et al [24]. Kiener et al [25] have provided an analysis of the strength properties on the basis of the small volumes of the materials that were tested.…”
Section: Crystal (Grain) Size-dependent Strengthsmentioning
confidence: 99%